The Effects of Imagery Among Karatedo Players in Selected Colleges and Universities in the Philippines: A Narrative Inquiry - Mortejo, Alonzo L (International Martial Arts and Culture Journal, 2024)
This study explores the lived experiences of collegiate Karatedo athletes in the Philippines who engaged in mental imagery as part of their athletic preparation. Using a narrative inquiry approach, the research investigates how athletes internalize and make sense of visualization techniques, particularly in enhancing performance readiness, confidence, and stress regulation. Data were gathered from in-depth narrative interviews with ten Karatedo athletes from five universities who completed an eight-week structured imagery program. Emerging stories reflect how athletes used imagery as a rehearsal space, a confidence builder, and a mechanism for emotional regulation. The study highlights imagery’s transformative influence on mental preparation, resilience, and identity formation in competitive martial arts. Findings emphasize the need for sport programs to adopt mental training techniques that are personal, reflective, and emotionally empowering.